Comparative Assessment of the Effectiveness of Interactive Teaching Methods in the Formation of Clinical Knowledge Levels - Аslonova Ibodat Jabborovna (American Journal of Biomedicine and Pharmacy, 2025)
The concept of “interactive” comes from the English “Interact” (“Inter” – “together”, “act” – “to influence”). Thus, “interactive methods” refer to the mutual interaction of students. “Interactive teaching methods” represent a form of activity in which students and teachers work collaboratively. The essence of interactive methods consists of mutual interaction among all students and the teacher [6,7]. One of the urgent tasks faced by professors and instructors of higher and special education institutions is training qualified and competitive professionals who do not lag behind in scientific and technical progress.